VERIFICATION OF A TRAIN ON RAILWAY TRACK SIMULATION AND OPTIMIZATION SYSTEM - Adam MAŃKA; Piotr KISIELEWSKI; Jarosław KONIECZNY; Krzysztof LABISZ; Janusz ĆWIEK (Transport Problems, 2023)
This article presents a Train on Railway Track simulation model and program developed by the authors. The model implements the module for multiple-criteria optimization with a set of proposed objective functions allowing reductions in train passing time, total costs, energy consumption, and adverse environmental impacts. The Train on Railway Track simulator has been developed to allow both the simulation itself and the ride optimization. The main achievement is the development of an algorithm that simulates the passage of a train over 500 km, the duration of which did not exceed two minutes. We present an analysis of the impact of model changes on the duration of the simulation and the accuracy of the results obtained. This allows the use of these achievements in simulations carried out for the railway, automotive, or aviation industries as well. Changes in the classical approach to optimization proposed by the authors made it possible to obtain results directly by solving classical systems of equations. The change in the approach to the optimization and system algorithm has reduced the operating time of the optimization system from thousands of simulations to a single simulation with an additional optimization process that takes several minutes to calculate. This article is a continuation of the description of the work performed, and basic information about the developed simulation model and software functionality is included in a separate publication [13].